2019
DOI: 10.1016/j.actbio.2019.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive factors for cartilage repair and regeneration: Improving delivery, retention, and activity

Abstract: Articular cartilage is a remarkable tissue whose sophisticated composition and architecture allow it to withstand complex stresses within the joint. Once injured, cartilage lacks the capacity to selfrepair, and injuries often progress to joint wide osteoarthritis (OA) resulting in debilitating pain and loss of mobility. Current palliative and surgical management provides short-term symptom relief, but almost always progresses to further deterioration in the long term. A number of bioactive factors, including d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 259 publications
(274 reference statements)
1
85
0
2
Order By: Relevance
“…In recent years, therapies based on stem cells have led to promising approaches for cartilage repair (Medvedeva et al 2018;Patel et al 2019). Laboratory and clinical studies have shown that mesenchymal stem cells (MSCs) can differentiate into chondrocytes and restore cartilage defects (Huang et al 2016;Driessen et al 2017;Ha et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, therapies based on stem cells have led to promising approaches for cartilage repair (Medvedeva et al 2018;Patel et al 2019). Laboratory and clinical studies have shown that mesenchymal stem cells (MSCs) can differentiate into chondrocytes and restore cartilage defects (Huang et al 2016;Driessen et al 2017;Ha et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Intra‐articular osteochondral fracture has a certain ability for self‐repair. After acute articular surface fracture, the defect of bone and cartilage is filled with fibrin clot. The defect area of the cartilage surface is in excess of 4 to 16 mm 2 , which is usually not the result of self‐repair.…”
Section: Discussionmentioning
confidence: 99%
“…They can also be easily functionalized for enhanced retention, and targeting. 88 Filova et al developed a cell-free hyaluronate/ type I collagen/fibrin composite scaffold containing polyvinyl alcohol (PVA) nanofibers. After taking advantage of enriching liposomes encapsulating bFGF and insulin, a time-controlled release of these two factors was observed; and successful stimulation for the cartilage regeneration was seen in vitro and in vivo.…”
Section: Physical Encapsulationmentioning
confidence: 99%